A Study on Procurement Function of Supply Chain Management in Small and Medium-Sized Enterprises in Pokhara Valley - Thagurathi, Rajesh Kumar (Journal of Nepalese Business Studies, 2008)
This paper has examined existing procurement practices, in the context of supply chain management, adopted by the Small and Medium-Sized Enterprises (SMEs) in Pokhara valley. The paper explored status of procurement section in the various organizations, examines the extent to which the information and communication technologies have been used for procurement, and presents the views of procurement personals on the impact of customer-supplier relationships on procurement function in formulating Supply Chain Management (SCM) initiatives. It has identified the potential paths for SMEs to improve their procurement practices. The Journal of Nepalese Business Studies Vol. IV, No. 1(2007)